2018
DOI: 10.1002/jin2.48
|View full text |Cite
|
Sign up to set email alerts
|

Nanodelivery strategies for the treatment of multidrug‐resistant bacterial infections

Abstract: One of the most important health concerns in society is the development of nosocomial infections caused by multidrug‐resistant pathogens. The purpose of this review is to discuss the issues in current antibiotic therapies and the ongoing progress of developing new strategies for the treatment of ESKAPE pathogen infections, which is acronymized for Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter species. We not only examine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 108 publications
(146 reference statements)
0
14
0
Order By: Relevance
“…[ 5 ] Biomedical devices containing antimicrobial metal nanostructures offer a promising microbicidal strategy in combating these extensively drug‐resistant pathogens and have received significant attention in both the academia and pharmaceutical industry. [ 6 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 ] Biomedical devices containing antimicrobial metal nanostructures offer a promising microbicidal strategy in combating these extensively drug‐resistant pathogens and have received significant attention in both the academia and pharmaceutical industry. [ 6 ]…”
Section: Introductionmentioning
confidence: 99%
“…Other studies also mentioned that metal nanoparticles, which naturally have antimicrobial properties, and their broad spectrum helped to carry AMPs for an effective treatment against MDR. A. baumanii, Streptococcus pyogenes, E. faecalis, K. pneumoniae , and P. aeruginosa (Jiang et al, 2018). Likewise, it was shown that alginate microparticles coated with hydroxymethylcellulose derivatives loaded with AMP can decrease hemolytic activity and increase bioavailability (Roque‐Borda et al, 2021).…”
Section: Nanobiotechnology As a Tool To Enhance Applicationmentioning
confidence: 99%
“…Very first biodistribution studies of early liposomes and PACA nanoparticles have revealed that intravenously injected man-made nano-objects were sequestrated by the immune system of the host [Gregoriadis, 1977, Couvreur et al, 1980a, Kante et al, 1980, Oppenheim, 1981. This found interest for targeting drugs to intracellularly infected macrophages [Fattal et al 1989, Abed and Couvreur, 2014, Abeb et al, 2015, Jiang et al, 2018 and to other liver disease such as liver cancer [Chiannilkulchai et al 1989, Reddy and Couvreur, 2011, Soma et al, 2012, Merle et al 2015, Lu et al, 2018. However, sequestration of nanoparticles by the immune system is a considerable obstacle to achieve drug delivery to disease tissues localized in organs that are not the main seats of the immune system.…”
Section: Designing Nanoparticles Controlling Their In Vivo Drug Delivmentioning
confidence: 99%